Violence Against Seniors as a Social Concern - Smetanová, Dorota (Kultura-Społeczeństwo-Edukacja, 2016)
Despite the fact that the situation in our society is sufficiently legally treated, the issue of domestic violence at the senior is still only in its infancy. Intervention and prevention would not only avoided tampering with this group of people, but to offer procedures that would help at least reduce the risk. The paper is focused on the issue of violence on seniors as society-wide problem. It defines domestic violence, causes, forms and types of violence. In the end, it offers opportunities for protection and prevention.